Теоретичний аналіз роботи сошника прямої сівби з адаптивними вертикальними дисками - Лузан, О. Р.; Артеменко, Д. Ю.; Лузан, П. Г.; Кісільов, Р. В.; Luzan, О.; Artemenko, D.; Luzan, P.; Kisilov, R. (ЦНТУ, 2025)
У статті наведено теоретичне обґрунтування роботи сошника прямої сівби з адаптивними вертикальними дисками в умовах технології No-Till. Розроблено розрахункову схему сошника, визначено систему сил та отримано аналітичні залежності для оцінки тягового опору. Сошник розглянуто як коливальну систему, побудовано амплітудно-частотну характеристику та проаналізовано вплив швидкості руху на стабільність глибини загортання насіння тощо. The aim of the article is to provide a theoretical justification of the operation of a direct seeding coulter with adaptive vertical discs under No-Till technology conditions. The study is focused on increasing the stability of seed placement depth, improving the quality of furrow formation, and reducing the energy consumption of the sowing process. Particular attention is paid to accounting for the force and dynamic interaction between the coulter, the soil, and crop residues under variable field conditions etc.
Theoretical Analysis of the Operation of a Direct Seeding Coulter with Adaptive Vertical Discs
Keywords: пряма сівба; сошник; адаптивні вертикальні диски; тяговий опір; сівалка; direct seeding; coulter; adaptive vertical discs; draft resistance; seeder